Interactions of Pt nanoparticles with molecular components in polymer electrolyte membrane fuel cells: multi-scale modeling approach. Issue 74 (22nd July 2016) - Brunello, Giuseppe F.; Lee, Ji Hye; Lee, Seung Geol; Choi, Ji Il; Harvey, David; Jang, Seung Soon
Abstract : Three phase model consists of Pt nanoparticles, Nafion, and graphite with oxygen, water, and hydronium. Abstract : In this study, a three-phase interfacial system of a fuel cell is simulated using a multi-scale simulation approach consisting of quantum mechanical density functional theory and molecular dynamics simulations. Through these simulations, the structural and transport properties of the three-phase system are investigated. The molecular interactions among the components of the three-phase interfacial system are examined by density functional theory and parameterized for potential energy functions of force field. First, we investigate the interactions of the Pt clusters with various molecules as a function of distance using the density functional theory method with dispersion correction. Based on the results of these calculations, a non-bonded interaction curve is built for each Pt–molecule pair. Such non-bonded interaction curves are reproduced by potential energy functions with optimized parameters. Based on these investigations, we develop a force field to describe the structures and transport properties of the Nafion–Pt–carbon (graphite) three-phase interfacial system using molecular dynamics simulations.